THE INFLUENCE OF CORPORATE SOCIAL RESPONSIBILITY ON FINANCIAL PERFORMANCE MEDIATED BY GREEN HUMAN RESOURCE MANAGEMENT - Dewi Khornida Marheni; Kelvin Kwek; Arienda Gitty Ramadani (LPSDI Bina Patria, 2024)
This study focuses on analyzing the implementation of Corporate Social Responsibility (CSR) strategies with a role through Green Human Resource Management (GHRM) on financial performance in hotels. The surveys were distributed via Google Forms to HR Managers, Front Office Managers, and Front Desk staff from luxury hotels in Batam City. This study utilized a one-shot study sampling approach, collecting data simultaneously over a specified period, aligning with the problem at hand. The analysis method employed in this study is Structural Equation Modeling (SEM) using the software called Smart-PLS. The test results indicate that customer value does not significantly affect financial performance. Furthermore, the results also reveal that society does not have a significant effect on performance. The insignificance of the CSR dimension concerning society and customers is noted regarding financial performance. The impact of implemented CSR activities by luxury hotels in Batam City has not been uniformly felt, possibly due to the influence of the Covid-19 pandemic, which has significantly impacted financial performance. However, when testing using other CSR dimensions, it is observed that GHRM has a positive impact on the financial performance of luxury hotels in Batam City